PENERAPAN MODEL PEMBELAJARAN TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN IPAS - husnah, Fidyatul; Musnar Indra Daulay; Muhammad Syahrul Riza; Nurmalina; Masrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low level of student learning activity during learning activities in class V UPT SD Negeri 007 Bangkinang City. This research aims to increase student learning activities by using the Jigsaw Type Cooperative learning model in learning in class V. This type of research is classroom action research carried out in two cycles, each cycle consisting of two meetings. The subjects of this research were 16 class V students, with 10 male students and 6 female students. The data collection techniques for this research are in the form of observation and documentation. The results of this research observation show that student activity in cycle I, meeting 1, was 61.95% in the sufficient category. In cycle I, meeting 2, student learning activities increased to 67.16% in the sufficient category. In cycle II, meeting 1, student learning activity increased to 73.40% in the good category. In cycle II, meeting 2, learning activities increased to 84.32% in the very good category. Thus it can be concluded that using the Jigsaw Cooperative learning model can increase student learning activities.